Prognostic value of pretreatment 18F-FDG PET/CT metabolic parameters in esophageal high-grade neuroendocrine carcinoma: A bicenter retrospective study - Hou, Guozhu; Zhao, Ningning; Li, Fang; Jing, Hongli; Zheng, Rong (Frontiers in Oncology, 2023)
Objective: The aim of this bicentric retrospective study was to assess the prognostic value of 18F-FDG PET/CT in patients with esophageal high-grade neuroendocrine carcinoma (NECs). Methods: From the database of two centers, 28 patients affected by esophageal high-grade NECs who underwent 18F-FDG PET/CT before treatment were retrospectively reviewed. Metabolic parameters (SUVmax, SUVmean, tumor-to-blood-pool SUV ratio (TBR), tumor-to-liver SUV ratio (TLR), metabolic tumor volume (MTV), total lesion glycolysis (TLG)) of the primary tumor were measured. Univariate and multivariate analyses were performed for progression-free survival (PFS) and overall survival (OS). Results: After a median follow-up period of 22 months, disease progression occurred in 11 (39.3%) patients, and death occurred in 8 (28.6%) patients. The median PFS was 34 months, and the median OS was not reached. Univariate analyses revealed that among metabolic parameters, only MTV and TLG were significant prognostic factors, while among clinical variables, only distant metastasis was a significant factor for both PFS and OS (P< 0.05). On multivariate analyses, MTV and TLG were independent prognostic factors for both PFS and OS (P< 0.05). Conclusions: In patients with esophageal high-grade NEC, MTV and TLG measured on pretreatment 18F-FDG PET/CT are independently prognostic factors for predicting PFS and OS, and might be used as quantitative prognostic imaging biomarkers.